Regulation of the sol Locus Genes for Butanol and Acetone Formation in Clostridium acetobutylicum ATCC 824 by a Putative Transcriptional Repressor - Nair, Ramesh V. (American Society for Microbiology, 1999)
A gene (orf1, now designated solR) previously identified upstream of the aldehyde/alcohol dehydrogenase gene aad (R. V. Nair, G. N. Bennett, and E. T. Papoutsakis, J. Bacteriol. 176:871–885, 1994) was found to encode a repressor of the sol locus (aad, ctfA, ctfB and adc) genes for butanol and acetone formation in Clostridium acetobutylicum ATCC 824. Primer extension analysis identified a transcriptional start site 35 bp upstream of the solR start codon. Amino acid comparisons of SolR identified a potential helix-turn-helix DNA-binding motif in the C-terminal half towards the center of the protein, suggesting a regulatory role. Overexpression of SolR in strain ATCC 824(pCO1) resulted in a solvent-negative phenotype owing to its deleterious effect on the transcription of the sol locus genes. Inactivation of solR in C. acetobutylicum via homologous recombination yielded mutants B and H (ATCC 824 solR::pO1X) which exhibited deregulated solvent production characterized by increased flux towards butanol and acetone formation, earlier induction of aad, lower overall acid production, markedly improved yields of solvents on glucose, a prolonged solvent production phase, and increased biomass accumulation compared to those of the wild-type strain.